Enhancing IT Change Management through Communities of Practice and Social Learning: A Case Study at a University - Marcel, Marcel; Kristiani, Evelline; Mudita, Damida Shu (Journal of Information Systems and Informatics, 2024)
As information technology (IT) is taking over numerous aspects of our lives, handling IT changes becomes more and more urgent for the higher education institutions. The study that aims to explore the influence of social learning within a Community of Practice (CoP) in IT change management at the University X in Jakarta was conducted. Through a case study approach that involves document analyses, semi-structured interviews, and participant observations, it was shown the pivotal role of CoPs in facilitating the IT changes by promoting social interaction and collaboration. The CoP can help to find the problem early and build a risk-reduction plan around it. This research finds that despite challenges maintaining consistent procedures, inter-departmental coordination, and the necessity of broadened training and communication, integrating CoPs with COBIT 2019 principles can offer a unified approach to IT transformation for the universities. The integration will allow universities to have better plan around changes in technology and offers practical examples for other higer education institutions.